2021
DOI: 10.1172/jci152264
|View full text |Cite
|
Sign up to set email alerts
|

Results of the CAPSID randomized trial for high-dose convalescent plasma in patients with severe COVID-19

Abstract: Background: COVID-19 convalescent plasma (CCP) has been considered a treatment option in COVID-19. This trial assessed the efficacy of neutralizing antibody containing high-dose CCP in hospitalized adults with COVID-19 requiring respiratory support or intensive care treatment.Methods: Patients (n=105) were randomized 1:1 to either receive standard treatment and 3 units of CCP or standard treatment alone. Control group patients with progress on day 14 could cross over to the CCP group. Primary outcome was a dic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(158 citation statements)
references
References 35 publications
(79 reference statements)
3
145
1
4
Order By: Relevance
“…In the TSUNAMI trial, 30-day mortality was 6.1% for the CP group and 7.9% for the control group. Published 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 and unpublished RCTs 10 , 11 , 12 have failed to demonstrate any benefit of CP on mortality with the exception of the study by O’Donnell et al 14 that found a significant reduction of 28-day mortality in patients receiving CP. In the RECOVERY trial, 4 the mortality rate was 24.1% and 24.4% in the CP group and control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the TSUNAMI trial, 30-day mortality was 6.1% for the CP group and 7.9% for the control group. Published 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 and unpublished RCTs 10 , 11 , 12 have failed to demonstrate any benefit of CP on mortality with the exception of the study by O’Donnell et al 14 that found a significant reduction of 28-day mortality in patients receiving CP. In the RECOVERY trial, 4 the mortality rate was 24.1% and 24.4% in the CP group and control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These striking differences are difficult to explain and are probably multifactorial: difference in the population's median age, difference in the risk factors for progression to severe COVID-19, time lapse between disease onset and CP transfusion, and differences in comprehensive patient management. It has been suggested that the benefits of CP may depend on the plasma NAb titer 9,13 and that using CP with a low titer could explain negative results. To our knowledge, TSUNAMI was among the first and few RCTs using qualified CP 25 The presence of anti-SARS-CoV-2 IgG antibodies in recipients before receiving CP has also been cited as a possible reason for lack of effect of CP.…”
Section: Jama Network Open | Infectious Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…After thoroughly reading the title and the abstract, unrelated literature on the convalescent plasma treatment of COVID-19 was excluded. After scrutinizing the studies based on the inclusion & exclusion criteria, a total of 14 randomized controlled trials and 4543 patients were included in the meta-analysis [ 2 , 7 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%